TATA KELOLA SAMPAH DI KOTA PEKANBARU (STUDI KASUS PADA BANK SAMPAH DI KOTA PEKANBARU TAHUN 2016) - Jery Nov Pratama; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In order to overcome the garbage problem in Pekanbaru City, referring to Government Regulation No. 81/2012 on Household Waste Management and Garbage of Household Garbage, Minister of Environment Regulation No. 13/2012 on Guidelines for Reduce, Reuse and Recycle Implementation through Waste Bank, and Pekanbaru City Regulation No. 8 Year 2014 on Waste Management, Pekanbaru Municipal Government together with the community work together in implementing waste management in Pekanbaru City through the application of 3R method and the establishment of Bank Trash. However, the application of 3R method and the establishment of Waste Bank is still not effective in overcoming the garbage problem in Pekanbaru City. This is due to the lack of awareness and knowledge of the community to participate in waste management in Pekanbaru City through the Garbage Bank program. In this research, there are two problem formulation: